2013
DOI: 10.1002/oby.20098
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Helicobacter pylori infection is associated with adverse metabolic traits in severely obese subjects

Abstract: Objective: Asian studies have reported on an association of Helicobacter pylori (Hp) infection with insulin resistance (IR) in normal-weight subjects. Whether such an association likewise exists in European subjects with severe obesity was questioned. Design and Methods: To address this question, 370 severely obese patients from our database were identified, who had undergone a gastroscopy with a histological examination of gastric mucosal biopsies and a concurrent assessment metabolic blood parameters as a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…A study [24] including 370 severely obese patients showed that the BMI of H. pylori-positive subjects did not differ from that of H. pylori-negative subjects. Ioannou et al [25] noted that the status of H. pylori/CagA antibody was not related with obesity.…”
Section: Discussionmentioning
confidence: 95%
“…A study [24] including 370 severely obese patients showed that the BMI of H. pylori-positive subjects did not differ from that of H. pylori-negative subjects. Ioannou et al [25] noted that the status of H. pylori/CagA antibody was not related with obesity.…”
Section: Discussionmentioning
confidence: 95%
“…Another 34 articles were excluded (12 were not observational studies, one did not include control group, one duplicate, and the other 20 did not report an outcome of interest). Subsequently, 18 studies including 15 cross‐sectional studies and three cohort studies involving 27 544 participants met our inclusion criteria and were included in the meta‐analysis. The search methodology is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Weight gain was observed across BMI ranges and was higher than control populations where H. pylori was not eradicated. Nineteen studies evaluated cross-sectional association of H. pylori and obesity (18)(19)(20)(21)(22)(23). Eleven studies found evidence of higher prevalence of H. pylori infection in obese individuals or metabolic impairment in the presence of the infection (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Infections Linked With Changed Body Mass Indexmentioning
confidence: 99%
“…While the numbers of studies in these additional categories are small, some results are trending in specific directions. For example, the prevalence of periodontal disease, respiratory Helicobacter pylori (6)(7)(8)(9)(10)(11)(12)(13)(18)(19)(20)(21)(22)(23) Eradication is associated with weight gain Ad36 (37,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)195) Associated with obesity and fat mass gain Post-surgical infections Higher incidence of surgical site infections, post-operative infections, deep sternal wound infections and blood stream infections in obese patients. Longer hospital stays and more readmissions in obesity Class 2 and 3 obesity (BMI > 35 and 40) is associated with more severe post-surgical infection.…”
Section: Is the Outcome Of Infection Different In Obesity?mentioning
confidence: 99%